Analisis Pendapatan Dan Nilai Tambah Bawang (Allium Cepa L) Merah Menjadi Bawang Goreng (Studi Kasus: Desa Togu Domu Nauli dan Kelurahan Timbang Galung Kabupaten Simalungun) - Haloho, Nurmita; Siregar, Rahma Sari (Universitas Galuh, 2026)
Togu Domu Nauli Village, Dolok Pardamean District, Simalungun Regency, is one of the areas with great potential as a shallot producer. Shallots planted by farmers are harvested at 65 days after planting. Shallot products can be improved and made more valuable by adding fried shallots, a type of processed shallot. Hadena MSME is a business unit engaged in processing shallots into fried shallots. Hadena MSME uses shallots as raw materials from Togu Domu Nauli Village as the highest producer of shallots according to Dolok Pardamean District data. The purpose of this study was to determine the income and added value of shallots into fried shallots. Sampling in this study was carried out using two methods, namely the Simple Random Sampling method for shallot farmers, and the saturated sampling method for Hadena Fried Shallot MSME business actors. Data analysis was carried out through the application of income analysis, as well as added value using the Hayami method. The study's findings reveal that shallot farmers in Togu Domu Nauli Village earn Rp 28,147,632 per planting season, while the Hadena Fried Onion MSME earns Rp 1,194,500 per production run. The added value of the Hadena MSME in Timbang Galung Village from processing shallots into fried onions is Rp 36,000 per kilogram.